Modelling Economic Growth in The Gambia: The role of Remittance and Inflation through ARDL Estimation - Minteh, Salim; Amadou Gissay; Touray, Katim (Universitas Bojonegoro, 2025)
This study explores the relationship between remittances received, inflation and economic growth in The Gambia using annual time series from 2003 to 2024. Employing the Autoregressive Distributed Lag (ARDL) bounds testing model to assess both shot-run and long-run interactions among variables. Remittance inflows have increased dramatically in The Gambia in the last two decades. The result confirms a long-run equilibrium with Error Correction Model (ECM) showing a negative and statistically significant coefficient, indicating a stable long run adjustment mechanism towards equilibrium. However, while remittances and inflation exhibit positive long-run effects on economic growth, these effects are statistically insignificant, suggesting that remittances are primarily directed towards consumption rather than productive investments, and that inflation impact maybe offset by other macroeconomic factors. To enhance the developmental impact of remittance inflows, the study targets financial instruments such as diaspora bonds, matched investment schemes, and remittance-supported business tax incentives. It also recommends inflation targeting policies to reserve purchasing power and macroeconomic stability. The originality of the study lies in its empirical application of the ARDL framework to the Gambia’s remittance and growth nexus, offering policy with a relevant insight for harnessing the financial inflows for sustainable economic development.